Audit of needlestick injuries in dental and dermatology sections: insights and strategies for safer practices - Ali Sadiq; Taimur Khalid; Fahad Umer; Hassan Yaqoob; Humayun Kaleem Siddiqui (Journal of the Pakistan Medical Association, 2026)
Objective: To assess the incidence of needlestick and sharp injuries among healthcare workers in dental and dermatology sections, to identify root causes, and to evaluate adherence to safety protocols. Method: The single-centre audit was conducted at the Aga Khan University Hospital, Karachi, and comprised data from the Department of Infection Prevention and Hospital Epidemiology and the institutional Adverse Event Management System from January 1, 2019, to December 31, 2020. The ‘Five Whys’ technique was used for root cause analysis and a fishbone diagram was generated to identify contributing factors of needlestick and sharp injuries reported in the dental and dermatology sections. Based on the findings, an improvement plan was developed using the Occupational Safety and Health Administration hierarchy of controls, which included workshops and training sessions aimed at enhancing safety practices. A follow-up audit was conducted from January 1, 2021, to December 31, 2022, to evaluate the effectiveness of the implemented measures. Results: In the first audit, 15 needlestick and sharp injuries were reported, with dental staff experiencing 12(80%) of them. The main causes included improper needle handling and recapping in the dental section, and cuts from surgical blades in the dermatology section. Post-intervention, the incidence of needlestick and sharp injuries decreased to 4 cases, with 3(75%) in the dental section. Conclusion: Critical gaps in safety protocols were identified in the first round of audit. The significant reduction in needlestick and sharp injuries post-intervention highlighted the effectiveness of quality improvement measures in enhancing occupational safety and reducing exposure to bloodborne pathogens. Key Words: Needlestick injury, Sharp injuries, Quality improvement, Occupational health, Infection control.